2005
DOI: 10.1007/s10495-005-0901-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential apoptotic pathways in human keratinocyte HaCaT cells exposed to UVB and UVC

Abstract: The induction of apoptosis in keratinocytes by ultraviolet (UV)-irradiation is considered to be a protective function against skin cancer. UV-induced DNA damage is a crucial event in UVB- and UVC-mediated apoptosis. However, the differences between the UVB- and UVC-induced apoptotic pathways remain unclear. Here we examine the differential mechanisms by which UVB and UVC irradiations induce keratinocyte apoptosis using human keratinocyte HaCaT cells. Differences in the production of (6-4)photoproducts ((6-4)PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 32 publications
7
71
0
Order By: Relevance
“…7 This hypothesis is in agreement with the reported sensitivity of p53-mutated HaCat cells to UVB irradiationmediated apoptosis. 30 In Figure 1, TA isoforms are more potent in Luciferase assays, especially the b and g isoforms, but we think that this should not be taken as an indication that p63 targets in apoptotic pathways S Borrelli et al procaspase-8 is more of a target of TA than DN isoforms: in fact, we have noticed this behaviour routinely, even in promoters characterized as bona fide targets of DNp63a. 13,14 It is likely that this effect is due to the properties of the transient assays, which are presumably not including chromatin constraints.…”
Section: Resultsmentioning
confidence: 87%
“…7 This hypothesis is in agreement with the reported sensitivity of p53-mutated HaCat cells to UVB irradiationmediated apoptosis. 30 In Figure 1, TA isoforms are more potent in Luciferase assays, especially the b and g isoforms, but we think that this should not be taken as an indication that p63 targets in apoptotic pathways S Borrelli et al procaspase-8 is more of a target of TA than DN isoforms: in fact, we have noticed this behaviour routinely, even in promoters characterized as bona fide targets of DNp63a. 13,14 It is likely that this effect is due to the properties of the transient assays, which are presumably not including chromatin constraints.…”
Section: Resultsmentioning
confidence: 87%
“…36) In addition, the activation of initiator caspase-9 was also observed in UV-irradiated HaCaT cells. 37) Our results showed that when HaCaT and NHEK cells were irradiated with UV, the cleavage of procaspase-3 and PARP was clearly detected 8 h after irradiation. These time courses of caspase-3 activation after UV irradiation show good correlations with the time courses of the appearance of apoptotic cells.…”
Section: Effect Of Eriodictyol On the Cell Viability Of Uv-irradiatmentioning
confidence: 52%
“…Reduction of UVB-induced apoptosis through inhibition of receptor clustering by keeping cells at low temperature (4 -10°C) during UVB irradiation or prevention of DISC formation by expressing a dominant negative FADD supports this notion (11,12). Correlation of apoptosis levels with DNA damage severity and reduction of apoptosis by enhancement of DNA repair enzymes (13,14) substantiates the idea that DNA damage induced by UVB irradiation activates the apoptotic pathway (6,15). While UVB is known to be an inducer of ROS formation (16,17) leading to apoptosis (18), the source of this ROS production is not precisely known.…”
mentioning
confidence: 62%